Understanding motivations of older women to continue or discontinue breast cancer screening - Susan C. Weller; Monique R. Pappadis; Shilpa Krishnan; Marsja R. Stearnes; Kristin M. Sheffield; Alai Tan; Jeffrey Z. Qi; James S. Goodwin (PLoS ONE, 2025)
Breast cancer screening guidelines indicate screening in women over 75 years of age is optional, depending upon patient health and preferences. To better understand the preferences and decision-making of older women, their experiences and perceptions concerning screening need to be linked to their intention to continue or discontinue screening. This study used a qualitative comparative analysis to identify the characteristics and themes linked to the intention to continue or discontinue screening. To capture the range of experiences and preferences, a purposive sample of community-residing adults (n = 59) was selected with equal representation of White, Black, and Hispanic women by age (70–74 years and 75 and older) and educational level (≤12 grade and >12 grade). In-depth qualitative interviews explored women’s perceptions of mammograms, the benefits and risks of screening, and personal screening experiences. Interviews were coded and quality-checked by two or more coders. A qualitative comparative analysis (QCA) identified combinations of personal characteristics and themes linked to the intention to continue (n = 32) or discontinue (n = 27) screening. Results indicated personal experiences were strongly linked to the intention to continue or discontinue. Women who mentioned recent screening (within three years) and either a spontaneously mentioned cancer story concerning a friend or family member or a doctor’s screening recommendation intended to continue screening (91% true positive rate, model sensitivity). Women who did not schedule screening and who did not mention a cancer story or a doctor’s recommendation (or neither) intended to discontinue screening (81% true negative rate, model specificity). These experiences transcended differences in race/ethnicity, age, and educational level. Continuation of breast cancer screening in older women is motivated by their personal screening history combined with cancer experiences and/or a doctor’s screening recommendation.